Islam and the Foundation of the State in Indonesia: The Role of the Masyumi Party in the Constituent Assembly the Perspective of Fiqh al-Siyāsah - Yusuf Adan, Hasanuddin; Iskandar, Iskandar; Ibrahim, Husaini; Helfianti, Sutri; Rosmawati, Rosmawati (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
At the commencement of Indonesian independence, the Masyumi Party was the sole prominent Islamic party. It attempted to include Islam as the foundation of the Indonesian state into its constitution. This study aims to investigate the effort of the Masyumi during their active participation and administration of the government throughout the Old Order period in the context of fiqh al-siyāsah. This research is a qualitative legal study employing the approach of fiqh al-siyāsah or Islamic politics. Meanwhile, data collection techniques were carried out through literature studies and in-depth interviews. The results of this study indicate that Masyumi's efforts in the Constituent Assembly, whose task is to draft the Indonesian State Constitution, were carried out very seriously and earnestly, causing the work of the Constituent Assembly members to drag on because there was no point of convergence between the Masyumi Islamic Party and the national parties. As a result of the absence of a meeting point, President Soekarno, with the support of the Indonesian Army, issued a decree on July 5, 1959, dissolving the Constituent Assembly and reverting to the 1945 Constitution. It turned out that the failure of Masyumi's hard work to make Islam the basis of the state was due to internal factors: communist, nationalist, and secularist ideology. In addition, it was also influenced by several external factors: the infiltration of the global superpowers and Islamophobia.  Despite the fact that Masyumi was deemed a failure, various contributions in the context of fiqh al-siysah in Indonesia, particularly resistance to communism, contributed color to an Islamic state administration system as well as adherence to the constitution and theistic democracy.